Comparison of recurrence rate, surgical time and pain score in primary pterygium excision with and without hydro-fluorescein tenonectomy - Min, Foo Lee (2023)
Purpose: To compare recurrence rate, surgical time, and pain score in primary pterygium excision with and without hydro-fluorescein tenonectomy. Methods: A prospective cohort study was conducted between February 2021 and January 2022 involving 80 patients. The sampling method was stratified sampling. The data collected was based on the surgical technique performed by the surgeon, which were primary pterygium excision with or without hydro-fluorescein tenonectomy. Outcome measures were duration of surgery, intraoperative pain score and recurrence of pterygium. Clinical assessment was performed on first week, third month and sixth month post operation. Pearson’s chi-square test was used to compare recurrence rate of two groups. Binary logistic regression was used to test the factors associated with recurrence rate. Mean surgical time and intraoperative pain score were compared between two groups using independent t-test. Results: The recurrence rates were 5.0% (two cases) and 22.5% (nine cases) in the with and without hydro-fluorescein tenonectomy group respectively (p = 0.023). Techniques and recurrence rate were related (OR 0.18, 95% CI 0.036, 0.90, p=0.037). Mean surgical times were 29.70 (± 8.35) minutes and 33.63 (± 12.16) minutes in the with and without hydro-fluorescein tenonectomy group respectively (p = 0.003). Subjects in hydro-fluorescein tenonectomy group experienced significantly less intraoperative pain compared to without hydro-fluorescein tenonectomy group, where mean pain scores were 2.05 (± 0.64) and 3.33 (± 1.83) respectively (p < 0.001). Conclusions: Hydro-fluorescein tenonectomy significantly reduces the recurrence rate, surgical time, and intraoperative pain score. Thus, it can be a technique option to take into consideration for pterygium surgery.